1989
DOI: 10.1021/jm00128a049
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and biological activity of novel carbacyclins having bicyclic substituents on the .omega.-chain

Abstract: A number of carbacyclins having bicyclic substituents on the omega-chain have been synthesized and tested for antiplatelet aggregation activity in vitro (against collagen-induced aggregation of rat platelet), for reduction of systemic blood pressure in vivo (ability to reduce the blood pressure in anesthetized rat by iv injection), and for cytoprotective activity (protection against ethanol-induced rat gastric lesion). The most effective compound for each activity was [3aS-[2E,3a alpha,4 alpha (3R),5 beta,6a a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 9 publications
0
23
0
Order By: Relevance
“…56 Pyrrolidynylbenzodioxanes have been shown to have affinities for a4b2 and a7 central nicotinic receptors which play a key role in a wide range of CNS functions, 57 and some 1,4-benzodioxanes have been shown to exhibit antiplatelet aggregation and organ-protective activities. 58 3 Biosynthesis of 1,4-benzodioxane oxyneolignans 1,4-Benzodioxane lignan natural products are usually found as racemic mixtures; steps B and C may not be enzymatically controlled and therefore for the most part a mixture of stereoand regioisomers are formed. 62 There is, however an important collective of 1,4-benzodioxanes, most notably the eusiderin and rodgersinine families that are found as single enantiomers in nature -resulting from a stereoselective coupling in step B.…”
Section: Additional Activitiesmentioning
confidence: 99%
“…56 Pyrrolidynylbenzodioxanes have been shown to have affinities for a4b2 and a7 central nicotinic receptors which play a key role in a wide range of CNS functions, 57 and some 1,4-benzodioxanes have been shown to exhibit antiplatelet aggregation and organ-protective activities. 58 3 Biosynthesis of 1,4-benzodioxane oxyneolignans 1,4-Benzodioxane lignan natural products are usually found as racemic mixtures; steps B and C may not be enzymatically controlled and therefore for the most part a mixture of stereoand regioisomers are formed. 62 There is, however an important collective of 1,4-benzodioxanes, most notably the eusiderin and rodgersinine families that are found as single enantiomers in nature -resulting from a stereoselective coupling in step B.…”
Section: Additional Activitiesmentioning
confidence: 99%
“…It has been shown that the biological activities are considerably influenced by the chirality of the 1,4-benzodioxane ring [22][23][24][25][26][27][28]. The enantiopure 2-substituted 2,3-dihydrobenzo-1,4-dioxins has been obtained from D-mannitol [29], by condensation of catechol with chiral glycidol [30] or epichlorhydrine [24a], by Sharpless epoxidation of 1-aryloxy-4-hydroxy-2-butene substrate [31] or by an enzymatic or chemical resolution of the racemic compound [32][33][34].…”
Section: 4-benzodioxanes and Bioisosteres Of The Non-aromatic Ringmentioning
confidence: 99%
“…[3] It has been shown that loxy)but-1-ene (4a), at room temperature in THF in the these biological activities are considerably influenced by presence of a palladium complex generated in situ by the chirality of the 1,4-benzodioxane ring. [2,7,[9][10][11][12][13][14][15] Enmixing Pd 2 (dba) 3 [tris(benzylideneacetone)dipalladium] antiopure 2-hydroxymethyl-2,5-dihydro-benzo [1,4]with dppb [1,4-bis(diphenylphosphanyl)butane] gave 2-dioxin is the usual starting material for the synthesis of vinyl-2,3-dihydro-benzo [1,4]dioxin (5) (Scheme 1) in optically pure 2-substituted 2,3-dihydro-benzo [1,4]diox-60% yield (Table 1, entries 1, 4 and 5). The cyclized ins.…”
Section: ] [2] [3] [4] [5] [6] Others Have Affinities With Reaction mentioning
confidence: 99%